New geographic distribution record of the phoretic association between the cerambycid beetle Acrocinus longimanus and the pseudoscorpion Cordylochernes scorpioides in the Colombian Amazonia (2016)
A case of phoretic association of the pseudoscorpion Cordylochernes scorpioides on the giant harlequin beetle Acrocinus longimanus is reported for the Colombian Amazonia. Despite the harlequin beetle reports for the area, no published records of this association are known for the Amazonia bioregion in Colombia. In March 2016, fifteen pseudoscorpions were collected from the upper abdomen of this beetle species in the municipality of Leticia, Amazonas department, Colombia. The need for reporting and publishing this type of interactions is highlighted.